The effectiveness of giving young coconut water in reducing dysmenorrhea symptoms: A case study of midwifery care - Dahniar, Dahniar; Fauziah, Putri; Marbun, Uliarta; Hasnaeni, Hasnaeni (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Dysmenorrhea is a common condition in women during menstruation, characterized by severe pain that can interfere with daily activities. The administration of medical therapy is often used to treat these symptoms, but natural approaches such as giving young coconut water are also starting to be considered. Objective: This study aims to analyze the effectiveness of giving young coconut water in reducing pain intensity in dysmenorrhea patients and provide an overview of the application of natural therapy-based obstetric care in patients with menstrual complaints. Methods: This study uses a case study design with a qualitative approach. The subject of the study was an adult woman who experienced primary dysmenorrhea. Data were collected through in-depth interviews, direct observation, and assessment of pain intensity using the VAS (Visual Analog Scale) scale before and after administering young coconut water. Result: The study showed a significant decrease in the intensity of dysmenorrhea pain after administering young coconut water. Before the administration of therapy, patients reported pain intensity at level 8 (scale 0-10), and after three days of administration of young coconut water, pain intensity decreased to level 3. Patients also reported feeling more comfortable and being able to continue their daily activities better. No significant side effects were found related to the consumption of young coconut water. I am injuring kei three mestiuia such does not feel jealous, the nature of the blood of meirah can bioactivity deingan good to know the absence of the current suidah in the absence of good. Conclusion: Giving young coconut water can be effective in reducing the symptoms of dysmenorrhea in patients who experience it. This therapy can be a safe and natural alternative to help relieve menstrual pain. It can be applied in obstetrics as part of a comprehensive approach to reproductive health care. Further research with larger samples is needed to reinforce these findings and explore the mechanism of action of young coconut water in dysmenorrhea